Nettle leaves-based sulfonated graphene oxide for efficient hydrolysis of microcrystalline cellulose. (15th January 2021) - Tondro, Hadiseh; Zilouei, Hamid; Zargoosh, Kiomars; Bazarganipour, Mehdi
Graphical abstract: Highlights: Nettle ( Urtica dioica L .) was used for newly synthesized sulfonated graphene oxide. Stacked graphene layers from iron-catalyzed graphitization of nettle leaves. Surface area 354.9 m 2 g −1 and total acid sites density 5.47 mmol g −1 were achieved. New catalyst was investigated in hydrolysis of untreated microcrystalline cellulose. 26.3% glucose yield and 72.8% selectivity were obtained. Abstract: A green preparation of porous graphitic carbon through iron based catalytic graphitization of nettle ( Urtica dioica L .) as precursor for the synthesis of sulfonated graphene oxide to be used as catalyst was developed. The morphological and physicochemical properties of nettle-derived porous graphitic carbon (GI-Ntt), graphene oxide (GO-Ntt) and sulfonated graphene oxide (sGO-Ntt) were assessed with several characterization techniques. Layered soft-structure with surface area of 354.9 m 2 g −1, mesopore volume of 0.13 m 3 g −1 and presence of high densities of functional groups such as hydroxyl, epoxy, carbonyl, carboxyl and sulfonic acid group with the total acid sites density of 5.47 mmol g −1 on the surface of the sGO-Ntt were observed. Moreover, it is revealed that GO-Ntt and sGO-Ntt both possess extremely thin nanosheet-like structures with an irregular edges and transparent lamella appearance unlike the GI-Ntt. Using the sGO-Ntt as catalyst, hydrolysis of microcrystalline cellulose (MCC) without pretreatment in water as an environmentally benign solvent resulted in the maximum glucose yield and selectivity of 26.3% and 72.8%, respectively. The optimum experimental conditions were sGO-Ntt concentration ratio of 1 g g −1 of untreated microcrystalline cellulose at 160 °C for 3 h.